To solve by substitution, you write an expression for one of the variables and use that expression in place of that variable in the other equation. Either of your equations can be solved easily for x.

x + 2y = 8

x = 8 - 2y (subtract 2y from both sides of the equation)

Now we can use this expression for x in the second equation.

x + 3y = 12

(8 - 2y) + 3y = 12 (after substitution of 8 - 2y for x)

8 + y = 12 (collect terms)

y = 4 (subtract 8 from both sides)

To find x, we substitute this value for y in the equation for x.

x = 8 - 2y

x = 8 - 2(4) (after substitution of 4 for y)

x = 8 - 8 (perform the multiplication)

x = 0 (perform the subtraction)

The solution is (x, y) = (0, 4).

x + 2y = 8

x = 8 - 2y (subtract 2y from both sides of the equation)

Now we can use this expression for x in the second equation.

x + 3y = 12

(8 - 2y) + 3y = 12 (after substitution of 8 - 2y for x)

8 + y = 12 (collect terms)

y = 4 (subtract 8 from both sides)

To find x, we substitute this value for y in the equation for x.

x = 8 - 2y

x = 8 - 2(4) (after substitution of 4 for y)

x = 8 - 8 (perform the multiplication)

x = 0 (perform the subtraction)

The solution is (x, y) = (0, 4).